Draft Annual Plan 2011-12 Volume-II Government of Uttarakhand - Planning Commission (Planning Commission, 2011)
Major Head/Sector wise Proposed Outlay for Annual Plan 2011-12 Gn Statement - A (Summary) Proposed Outlay Annual Plan - 2011-12 Annual Plan 2011-12 Proposed Outlay (Scheme wise) Physical Targets and Achievements Statement Regarding Externally Aided Projects Annual Plan 2011-12 Bharat Nirman Programmes - Proposed Outlay Centrally Sponsored Schemes (CSSs) Tribal Sub Plan (TSP)-I Annual Plan 2011-12-Financial Outlays : Proposals for TSP.
State Planning Commission Government of Uttarakhand